Introduction to the Pasigala Website-Based Historical Site - Rizka Fadliah Nur; Muliadi (Jurnal Teknologi Informatika dan Komputer, 2026)
History is one of the cultural heritages that holds significant value in shaping the identity of a nation. Historical sites serve as silent witnesses to the passage of time and store a wealth of valuable information about past civilizations, cultures, and events. This research aims to design and develop a website-based historical site information system for the Pasigala area (Palu, Sigi, Donggala). This system functions as an interactive digital medium that provides comprehensive information about historical sites, with the goal of increasing public awareness of the importance of preserving local culture and supporting the promotion of historical tourism. With the website-based information system, the public can easily access accurate and reliable information about the historical sites in Pasigala. The research method used is Research and Development, with stages including literature review, primary and secondary data collection, needs analysis, and design. With a website-based information system, the public can easily obtain accurate and reliable information about historical sites in Pasigala. The system includes development, testing, and implementation. The result is a responsive web-based application that contains complete data on historical sites along with a photo gallery, and allows user interaction through a suggestion feature. The system has also been tested for functionality and usability with satisfactory results. This research contributes to the preservation of cultural heritage in the digital era while supporting the development of information technology, particularly in the field of website-based information systems.